Nuclear behavior in exconjugants of Paramecium bursaria - Yang, Xianyu; Gao, Xin; Song, Yuanpu (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2018)
Paramecium bursaria is the representative of “bursaria” group of Paramecium, whose nuclear behaviour during conjugation is quite different from other species. In its exconjugants, there are three types of nuclei, a parental macromicleus (pMac), two macronuclear anlagen (MA) and two presumptive micronuclei (Mic). According to the previous studies, both Mic and MA distribute equally during exconjugant division — each daughter cell receiving a Mic and a MA, which never happens in other Paramecium species studied so far. Meanwhile pMac sustains even in daughter cells. To clarify these issues, nuclear behavior in exconjugants of P. bursaria was studied by staining with carbol fuchsin solution. As the results, degeneration of one presumptive Mic as well as pMac in P. bursaria exconjugant was observed indicating different nuclear development pattern from previous reports.